2008
DOI: 10.1016/j.ijsu.2008.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Advanced enteral therapy in acute pancreatitis: Is there a room for immunonutrition? A meta-analysis

Abstract: There is no evidence that enteral nutrition supplemented with glutamine, arginine and/or omega-3 fatty acids, in comparison with standard enteral nutrition, has any beneficial effect on infectious complications, mortality or length of hospital stay in acute pancreatitis. The pursuit of new compositions of enteral formulations in this category of patients may be advocated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 38 publications
2
31
0
4
Order By: Relevance
“…O conceito implica em indicar-se adequadamente cada imunonutriente, tais como glutamina, selênio, óleo de peixe (ácidos graxos -3) e arginina, a cada situação clínica, entre elas desnutrição, queimaduras, trauma, pacientes em estado crítico ou em síndrome de estresse respiratório agudo. Basearam sua argumentação no fato que os diversos estudos apresentados até o momento incorrem em erros metodológicos diversos, como seleção inadequada da amostra para estudo, uso de produtos para o estudo que associam diversos imunonutrientes 2,4,13,17,28,35,38,43 . Nesta linha de raciocínio, alguns autores estão buscando limitar o foco da amostra.…”
Section: Discussionunclassified
“…O conceito implica em indicar-se adequadamente cada imunonutriente, tais como glutamina, selênio, óleo de peixe (ácidos graxos -3) e arginina, a cada situação clínica, entre elas desnutrição, queimaduras, trauma, pacientes em estado crítico ou em síndrome de estresse respiratório agudo. Basearam sua argumentação no fato que os diversos estudos apresentados até o momento incorrem em erros metodológicos diversos, como seleção inadequada da amostra para estudo, uso de produtos para o estudo que associam diversos imunonutrientes 2,4,13,17,28,35,38,43 . Nesta linha de raciocínio, alguns autores estão buscando limitar o foco da amostra.…”
Section: Discussionunclassified
“…Very important is the local effect of nutrition in the gastrointestinal tract and its impact on the body's defense mechanisms. It is known that the mucosa of the gastrointestinal tract tissue is 65% of the immune system tissue and its proper functioning depends on the presence of nutrients in the gut, which is the most potent stimulator of defense processes [3,14]. Otherwise the maintenance of normal immune function of the body plays an important role in maintaining the continuity and integrity of the gastrointestinal tract.…”
Section: Malnutritionmentioning
confidence: 99%
“…Implementation of parenteral nutrition should be considered in the course of severe acute pancreatitis [4]. Opinions about using mixtures enriched with immunomodulating compounds remain controversial [4,14,29,30]. Ping et al found that the implementation of an intravenous infusion of L-alanyl glutamine at the start of hospitalization significantly reduced the incidence of complications of acute pancreatitis compared to the start of this treatment after 5 days.…”
Section: Use Of Immunonutritionmentioning
confidence: 99%
“…Petrov i wsp. [50,51] przedstawili obszerne metaanalizy porównujące różne-go rodzaju metody i sposoby żywienia oraz skład żywie-nia stosowany u chorych z OZT. Stwierdzili, że stosowanie dojelitowo żywienia immunomodulującego zawierającego glutaminę, argininę i kwasy omega-3 w stosunku do innych rodzajów żywienia dojelitowego, w tym standardowego, nie wpływa istotnie na zmniejszenie liczby powikłań infekcyjnych, śmiertelność i czas pobytu w szpitalu.…”
Section: Choroby Trzustkiunclassified